Role of Notary In Implementation of The Principle of Nemo Plus Juris and Itikad in Transfer of Rights to Land as a Basis of Evidence for Owners - Sawin Dwi Hapsari (Jurnal Akta, 2020)
Land is a social symbol in society where control of a plot of land also symbolizes the value of honor, pride and personal success so that economically, socially and culturally, the land owned becomes a source of life, a symbol of identity, the rights of honor and dignity of its supporters so that it is necessary, registration arrangements land as the implementation of control of ownership rights over the land. Because land has economic value, land rights are traded or rights can be transferred through grants, buying and selling, inheritance and others. The transfer of land rights is usually carried out through the process of making a deed, either a sale and purchase deed, a deed of inheritance or a deed of grant signed by the parties having an interest in the transfer of rights to the land. And the making of the deed of transfer of land rights must be carried out in the presence of a notary / official who makes land deeds, so that the deed of transfer of land rights can have evidentiary power either as deeds in the judicial system or deeds that serve as the basis for making certificates. In the transfer of land rights, the principle of nemo plus juris is known, which protects the real rights holder and the principle of good faith, which means protecting people who in good faith obtain a right from the person suspected of being the legal right holder. This principle is used to provide evidentiary power for maps and public lists that exist in the Land Office.